Descending Facilitation Maintains Long-term Spontaneous Neuropathic Pain - Wang, Ruizhong (2013)
Neuropathic pain is frequently characterized by spontaneous pain (i.e. pain at rest) and in some cases, cold and touch-induced allodynia. Mechanisms underlying the chronicity of neuropathic pain are not well understood. Rats received spinal nerve ligation (SNL) and were monitored for tactile and thermal thresholds. While heat hypersensitivity returned to baseline levels within approximately 35-40 days tactile hypersensitivity was still present at 580 days after SNL. Tactile hypersensitivity at post-SNL day 60 (D60) was reversed by microinjection of (a) lidocaine or (b) a CCK2 receptor antagonist into the rostral ventromedial medulla (RVM) or (c) dorsolateral funiculus (DLF) lesion. RVM lidocaine at D60 or spinal ondansetron, a 5HT(3) antagonist, at post-SNL day 42 produced conditioned place preference (CPP) selectively in SNL treated rats, suggesting long-lasting spontaneous pain. Touch-induced FOS was increased in the spinal dorsal horn of SNL rats at D60 and prevented by prior DLF lesion suggesting that long-lasting tactile hypersensitivity depends upon spinal sensitization, which is mediated in part, by descending facilitation, in spite of resolution of heat hypersensitivity. PERSPECTIVE: These data suggest that spontaneous pain is present for an extended period of time and, consistent with likely actions of clinically effective drugs, is maintained by descending facilitation.